LGBTQ+ and African Ethics: Between Tradition and Human Rights (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
The discourse on LGBTQ+ identities and rights has gained increasing prominence across the globe, including in African societies, necessitating philosophical reflection. While human rights frameworks advocate for inclusivity and acceptance, traditional African ethics largely view sexuality through the lens of communal values and natural order. This tension raises critical questions about African cultural identity, morality, and the evolving influence of globalisation. Employing the methods of analysis and phenomenology, this paper argues that the LGBTQ+ movement, though presented as a universal human rights struggle, is largely shaped by Western ideologies that may not align with African ethical thought. Furthermore, it contends that if left unchecked, the growing acceptance of LGBTQ+ identities could significantly erode Africa’s traditional moral values on sexuality, already weakened by modernity and digital influence. The paper concludes that while human dignity is universal, an African philosophical anthropology rooted in communal ethics and moral education can provide a framework for addressing this complex issue in a manner that preserves African identity and values.